The In vivo Effects of Caffeine on the Hypoglycemic Activity of Gliclazide and Metformin in Healthy Rats - Mohiuddin, Mohammad; Amran, Md Shah; Hossain, Md Amjad (Dhaka University Journal of Pharmaceutical Sciences, 2010)
An in vivo study has been conducted to observe the effects of caffeine on the hypoglycemic activity of gliclazide and metformin HCI in rats. For this, healthy rats weighing about 250±25 g were used and the blood sugar levels were measured after administration of a drug alone and in combination. Diabetes was induced in rats by administration of alloxan at a dose of 40 mg/kg body weight. Drugs were administered in rats and were observed for four weeks. The blood sugar levels were estimated in two stages; firstly, after two week and secondly, after four week of administration of drug. It was found that the hypoglycemic activities of both gliclazide and metformin HCl were potentiated by concurrent application of caffeine and either of the drugs, but the extent of potentiation was more in case of metformin HCI as evident from the blood sugar level of rats. Key words: Caffeine; Gliclazide; Metformin; Diabetes; Alloxan; Blood sugar; Rats. DOI: 10.3329/dujps.v8i1.5335 Dhaka Univ. J. Pharm. Sci. 8(1): 47-51, 2009 (June)